Critical Analysis of Discipline Character Building through Discipline Week Activities for Students of Muhammadiyah 4 Banjarnegara Elementary School - Laily Afiya; Ine Kusuma Aryani; Wakhudin Wakhudin (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
This study aims to analyze the formation of the disciplinary character of grade 4 and 5 students at SD Muhammadiyah Banjarnegara. One way to shape the character of discipline is by carrying out Discipline Week activities, a collaboration between the school and Kodim 0704 Banjarnegara. With the implementation of the program, it is expected that the discipline of students will increase significantly. Discipline is an important attitude that affects the success of students both in the present and the future. This research uses the qualitative descriptive method of case study type. Data collection techniques are carried out by means of interviews, observation and documentation. In this case, researchers use data validity tests using triangulation techniques. The results showed that the activities of Discipline Week were carried out well and effectively. This activity can motivate students to be disciplined in time and behavior.